Sustainable development : papers presented to CEDA seminar series on Sustainable Development, Sydney, April 2003 - February 2004. (Information paper (Committee for Economic Development of Australia), 2004)
Includes the following papers: The business case for sustainability -- Corporate sustainability : an investor perspective -- Sustainable transport in sustainable cities -- Mining and sustainable development.